Pengaruh Perendaman Benih terhadap Perkecambahan dan Pertumbuhan Tanaman Hanjeli (Coix lacryma-jobi L.) - Irwan, A.W.; Sunarto, T.; Wahyudin, A. (Jurnal Agroteknologi (Agronu), 2026)
Job's tears is a crop that has a big nutritional value so it needs to be developed, one of the obstacles in Job's tears cultivation is that the seeds have a thick skin that inhibits the germination process. To overcome this, namely by treating different soaking temperatures. This study aims to determine the response of germination and growth of Job's tears plants using several soaking temperatures, this was carried out at the Rancaekek Village Garden, Bandung Regency from June 2025 to October 2025 using a Randomized Block Design (RAK) namely soaking seeds at different temperatures, namely s0 (without soaking), s1 (ordinary water), s2 (temperature 30°C), s3 (temperature 40°C) and s4 (temperature 50°C) with each treatment repeated 5 times. The parameters observed were germination power, growth rate and maximum growth potential while the vegetative growth parameters included crop height, ILD and crop crease weight. The results of the study showed that germination power (66.4%), growth rate (0.98%/day) and maximum growth potential (39.67%) showed that treatment s2 gave an average value that tended to be higher compared to s0, s1, s3, and s4. Treatment s1 tended to have a better effect on observations of plant height 10 WAP (40.75 cm), crop height 12 WAP (70.45 cm), crop height 14 WAP (85.58 cm), plant height 16 WAP (94.27 cm), ILD (4.29) number of leaves (55.1), and dry weight per plant (512 g). With the right seed soaking treatment, germination can be accelerated and the growth of job's tears can be increased